INCREASING BRAND AWARENESS THROUGH CONTENT MARKETING - Silvia Ekasari; Oskar Hutagaluh (CV. Adiba Aisha Amira, 2024)
In an increasingly competitive digital age, increasing brand awareness is both a challenge and a vital necessity for every business. Content marketing has emerged as an effective strategy to address this challenge. The research method in this study uses literature. The results revealed that the success of content marketing depends on several key factors: a deep understanding of the target audience, consistency in the production and distribution of high-quality content, optimisation for search engines (SEO), and seamless integration with other digital marketing strategies. The study also identifies common challenges in content marketing implementation, including difficulties in measuring ROI, maintaining content consistency, and competing in an increasingly crowded content landscape.